KnowledgeBoat Logo

Mathematics

Show that :

cos2(45°+θ)+cos2(45°θ)tan (60° + θ) tan (30° - θ)=1\dfrac{\text{cos}^2 (45° + θ) + \text{cos}^2 (45° - θ)}{\text{tan (60° + θ) \text{tan (30° - θ)}}} = 1

Trigonometrical Ratios

21 Likes

Answer

Solving, L.H.S. of the equation, we get :

cos2(45°+θ)+cos2(45°θ)tan (60° + θ) tan (30° - θ)cos2(45°+θ)+sin2[90°(45°θ)]tan (60° + θ) cot [90° - (30° - θ)]cos2(45°+θ)+sin2(45°+θ)tan (60° + θ) cot (60° + θ)As, cos2 A + sin2A=1 and tan A. cot A=1111.\Rightarrow \dfrac{\text{cos}^2 (45° + θ) + \text{cos}^2 (45° - θ)}{\text{tan (60° + θ) \text{tan (30° - θ)}}} \\[1em] \Rightarrow \dfrac{\text{cos}^2 (45° + θ) + \text{sin}^2 [90° - (45° - θ)]}{\text{tan (60° + θ) \text{cot [90° - (30° - θ)]}}} \\[1em] \Rightarrow \dfrac{\text{cos}^2 (45° + θ) + \text{sin}^2 (45° + θ)}{\text{tan (60° + θ) \text{cot (60° + θ)}}} \\[1em] \text{As, cos}^2 \text{ A + sin}^2 A = 1 \text{ and tan A. cot A} = 1 \\[1em] \Rightarrow \dfrac{1}{1} \\[1em] \Rightarrow 1.

Since, L.H.S. = R.H.S.

Hence, proved that cos2(45°+θ)+cos2(45°θ)tan (60° + θ) tan (30° - θ)=1\dfrac{\text{cos}^2 (45° + θ) + \text{cos}^2 (45° - θ)}{\text{tan (60° + θ) \text{tan (30° - θ)}}} = 1.

Answered By

14 Likes


Related Questions